Implementasi Dakwah H. dr. Nurul Kawakib, Sp.B., Finacs. dalam Praktek Operasi terhadap Paseien dengan Pendekatan Spiritual Sebagai Proses Holistik Terapi - Halimatus Sya’diyah; Imam Syafi'i (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2021)
In a dhohir way, doctors are heroes who heal various illnesses with the talent and flexibility of medical knowledge that they master. For years they have studied medicine at a cost that is not small. However, it was successfully pursued by the encouragement of desire, struggle as well as efforts that supported each doctor. Reaching dreams to help people in need. Reap the results and practice knowledge. In this scientific work later, the author will witness firsthand how a doctor's surgical operations practice to patients by using da'wah with a media called spiritual approach as a holistic process and how the interaction between pre-surgery and post-surgery patients. This study aims to reveal and find out the implementation of the da'wah of a surgeon to surgery patients. In this study, researchers used qualitative methods. Qualitative method is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. One thing that cannot be denied is that humans in their lives will never be able to separate themselves from other humans. As for this alms is also the application of the doctor's da'wah. This method is an act of helping others, especially those who are more in need. Because human nature cannot live alone. He needs other people in his life.